Остеологічні матеріали із культових комплексів Ольвії - Журавльов, О.П.; Маркова, О.В. (Археологія, 1995)
У статті подається характеристика та порівняльний аналіз остеологічного матеріалу із культових комплексів Ольвії — ботросів. В статье впервые за всю историю археозоологических исследований Ольвии рассмотрены остеологические материалы из закрытых комплексов культового назначения — ботросов, найденных на раскопах АГД и Е3. Установлено, что эти материалы и количественно, и качественно отличались от материалов из синхронных ботросам культурных слоев Ольвии. В частности, в первых преобладали одни части скелета, во вторых — другие. Есть различия и в видовом составе. Видимо, к культовой мясной пище предъявлялись иные требования, чем к повседневной. It is the first case in the history of archaeozoological studies of Olbia that osteological findings from closed assemblages of cult purposes (botroses) found in excavations AGD and Е3 are described. It is stated that these findings differ both quantitatively and qualitatively from findings excavated from cultural Olbian layers synchronous to botroses. In particular, certain parts of skeleton prevailed in the former, while other parts prevailed in the latter. There are differences in the species composition as well. Apparently, demands made to the celt meat food differed from those to everyday food.